Anticipation, informative tool to join for journalism and health - Cachán-Alcolea, Carlos (Revista Española de Comunicación en Salud, 2019)
Journalism aim is to inform about what happens. But it also deals -or may deal – with what have happened, will happen and what people think. Among all the events that occur every day in the world, the ones related to health have a great importance for human beings. The internet has brought the domain of immediacy – here and now- that produces information about health without analysing the keys to understand what happen and what could happen. With the anticipation, journalism analyses in depth past and present information, to discover implications. It observes the causes, finds out new data and looks for new approaches and predicts consequences. Anticipation journalism isn’t base on conjectures o journalist’s prophecies. Provides background information on facts that didn’t occur, but whose media genes permeate present reality. It seeks human interest on future health events, providing quality information and trying to respond when it would happen and what consequences will bring to the receivers, their family, environment and the world. This way, anticipation becomes a journalistic tool that join journalism and health.